Letter from M. F. Borzano to James Curtis Booth - Borzano, M. F. (1851)
Discussion of a "McCulloh" process for refining of gold, named for Richard Sears McCulloh (1818 – 1894) an American civil engineer and pupil of James Curtis Booth (1810-1888) from 1838 to 1839.
Keywords: Booth, James Curtis, 1810-1888; United States Mint; Mint of the United States; Metals--Refining; Borzano, M. F.; McCulloh, R. S. (Richard Sears), 1818-1894